PENGARUH METODE OUTDOOR STUDY TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI SISWA KELAS IV SDN 36 PONTIANAK - Supiani, Supiani; Kaswari, Kaswari; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe aim of this research was to investigate the influence of outdoor study method on writing skill of descriptive essay to 4 students of SDN 36 South Pontianak. Research method on this research was experimental, and it was in form of pre-experimental design, with one-group pretest-posttest design. The population was all 4 students of SDN 36 South Pontianak, which were 56 students. The sample collecting technique was simple random sampling. The sample of the research was 4 students of class B which were 27 students. The data collecting technique used was measuring technique. The data collecting tool was a test. Based on the result of data analysis, it was found that the average score of pre-test was 37,157 and post-test was 43,083. The result of the analysis of dependent t-test was tobtain (9,481) > ttable (2,056). Due to tobtain (9,481) > ttable (2,056), thus Ha was accepted. Therefore, it was found that outdoor study method had a significant effect toward students writing skill on descriptive essay. The result of the ES wasÂ =0,561 (moderate effect). It showed that outdoor study method had significant effect toward students writing skill on descriptive essay with moderate effect.Â Keywords: Influence, Outdoor Study Method, Descriptive Essay